The new paternalism: over-indebtedness and non-rational borrowing from a behavioural economics perspective - Szabó, Zoltán (Marketing & Menedzsment, 2019)
AIM OF THE PAPER Our paper discusses the idea of the new paternalism, including its development over recent years, its characteristics and the tools which it provides for governments to steer decisions. The idea of the new paternalism is based on the claim that, to achieve our own true preferences, there is a need for relatively modest adjustments to decision-making. Certain core neoclassical values have also been retained - for example, freedom of choice is acknowledged as an important safeguard against government error. METHODOLOGY In respect of methodology, we undertook a serious review of the literature. Further, the basic psychological phenomena which characterise our decision-making processes and the theoretical debate on the new paternalistic approach are also interpreted - arguments in favour of its wide implementation, as well as concerns over its legitimacy. MOST IMPORTANT RESULTS The main result of our review is that this new economic policy approach, which is based on behavioural economics-related findings, should be discussed as widely as possible. It is, nevertheless, also important to underline the critical thoughts of the new light or libertarian paternalism. Here we concentrate mainly on two streams of criticism: the discoverability of people’s true preferences and the rationality of politicians. RECOMMENDATIONS We focus on the possible fields of application of the new paternalistic approach: over-indebtedness and non-rational borrowing. Several ways of how libertarian paternalistic tools can be applied to these issues are listed, but, more significantly, the limits of these application possibilities are emphasised.